Noninvasive mechanical ventilation - (:unkn) unknown (MARMARA UNIV, FAC MEDICINE, 2016)
Noninvasive mechanical ventilation (NIMV) has been widely applied to the patient with respiratory failure since 1990's around the world. The respiratory function of the patient with respiratory failure should be supported by using positive pressure ventilation until primary problem of the patient is treated. Positive pressure should be given noninvasively or invasively. If the patient is conscious (except unconsiousness due to CO2 retention) and has intact bulber function(sufficient cough reflex and swallowing function) and has stable clinical picture, we have to use NIMV instead of invasive mechanical ventilation (IMV). NIMV can be applied to the patient outside of the intensive care unit. The side effects of mechanical ventilation are significantly decreased during NIMV than that of IMV.
Keywords: Noninvasive ventilation; Respiratory insufficiency